Job Satisfaction as a Mediator of Organizational Culture, Motivation, and Teacher Performance in Vocational High Schools - Indayani, Kadek; Heryanda, Komang Krisna; Telagawathi, Ni Luh Wayan Sayang (Universitas Pendidikan Nasional, 2025)
This study aims to examine the direct and indirect effects of organizational culture, motivation, job satisfaction and teacher performance at SMK Bintang Persada Denpasar. Causal design is used to examine the causal relationship between variables that influence and variables that are influenced. Data collection used is survey, interview, and documentation. The results of the study were further analyzed using path analysis so that it would be analyzed with a Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that organizational culture, motivation, and job satisfaction had a direct effect on teacher performance at SMK Bintang Persada Denpasar. The existence of this influence is illustrated by the condition of teachers who have an innovative nature tend to seek and apply new and more effective learning methods, which not only improve the quality of teaching but also improve students' learning experience. Innovations made by teachers are driven by high motivation to produce quality learning. The quality of quality learning is shown by learning that is more organized and structured in planning. The implementation of good learning cannot be separated from the role of superiors in carrying out the role of supervision of learning implementation. Where supervision is carried out as an evaluation of the implementation of learning carried out by teachers in the classroom. The evaluation carried out by superiors is solely to create quality learning. The results of the evaluation can be used as a reference for teachers' self-reflection on the role they play. The reflection in question is in the teacher's role as a designer and implementer of learning in the classroom. The implementation of learning well has an impact on the accuracy of a teacher's task completion. The achievement of task completion accuracy is a picture of good teacher performance. Lack of innovation in the classroom, declining quality of relationships between teachers and students, and a reduced sense of responsibility for student success. As a result, the learning process is not optimal and educational outcomes are unsatisfactory. To improve teacher job satisfaction, it is important to create a supportive work environment and provide appropriate rewards. Therefore, further research that considers long-term factors as well as the dynamics of policy and the broader education environment will provide a fuller picture of how organizational culture and motivation can affect teacher performance in a sustainable way.